Peningkatan Minat Baca Bagi Siswa MI Menggunakan Metode “ABACALAH” Berbasis Komunitas - Khumaidi Abdillah; Siti Aisah (TAAWUN, 2022)
The purpose of this community based is to increase the interest in reading by MI students using the community-based "ABACALAH" method. The method in community based is partnership-based. The location of this community service is carried out at MI Hayatul Ulum Pangean Maduran lamongan East Java. This form of community service activity is in the form of mentoring, providing motivation, lectures, and discussions. The result of this community service is that students are motivated and increasingly active in reading because this service also provides books collectively, as well as adding books in the school library. During the service activity, students were very enthusiastic in solving several questions provided. Based on the community service activities that have been carried out, it can be concluded that this service program runs in accordance with the purpose of the activity, namely students are motivated when they are guided to read both fiction and nonfiction books